Antimicrobial Properties of Fennel By-Product Extracts and Their Potential Applications in Meat Products - Marica Egidio; Loriana Casalino; Filomena De Biasio; Marika Di Paolo; Ricardo Gómez-García; Manuela Pintado; Alma Sardo; Raffaele Marrone (MDPI AG, 2024)
Background: Beef burgers are perishable meat products, and to extend their shelf life, EU Regulation 1129/11 permits the use of certain additives. Objectives: However, given the concerns of health-conscious consumers and the potential toxicity of synthetic substances, this study aimed to explore the use of fennel waste extracts as natural preservatives. Methods: This study characterized the bioactive compounds (phenolic content), the antioxidant activity (ABTS+ and DPPH assay), and the antimicrobial properties (against Salmonella enterica serotype Enteritidis, Escherichia coli, Staphylococcus aureus, Bacillus cereusi, and Pseudomonas aeruginosa) of different fennel waste extracts (LF, liquid fraction; SF, solid fraction and PF, pellet fraction). Additionally, the potential use of the best fennel extract was evaluated for its impact on beef burger shelf life (up to 18 days at 4 ± 1 °C) in terms of microbiological profile, pH, and activity water (aw). Results: The PF extract, which was rich in flavones, hydroxybenzoic, and hydroxycinnamic acids, demonstrated the highest antioxidant and antimicrobial activities. Microbiological analyses on beef burgers with PF identified this extract as a potential antimicrobial substance. The aw and pH values did not appear to be affected. Conclusions: In conclusion, fennel extracts could be proposed as natural compounds exploitable in beef burgers to preserve their quality and extend their shelf-life.